A new species of Phrynus Lamarck, 1801 (Arachnida: Amblypygi), from Trinidad and Tobago, and Venezuela, with a redescription of Phrynus pulchripes (Pocock, 1894) - Joya, Daniel Chirivi (Zootaxa, 2017)
We present the description of Phrynus calypso sp. nov. from Trinidad and Tobago, and Venezuela This species is very similar to Phrynus pulchripes (Pocock), however after examining Colombian specimens of P. pulchripes (ca. type locality), many differences were found. Characters commonly used in diagnosis of Phrynus species are variable and make identification difficult. Differences in a few structures, like pedipalpal spines, could not be enough to provide a useful diagnosis. It is necessary to account for variation of similar species in conjunction, and select non overlapping groups of characters. Observations in the variation in both species are presented, pointing out sources of confusion, and suggesting alternative characters to support diagnoses. At the moment, details about variation in many species in Phrynus, like that of P. pulchripes, are poorly known, and for this reason a redescription is provided.